Software processes improvement proposal based on PSP for telecommuting contexts (2019)
This article presents a proposal for improving the software process in telecommuting contexts based on the Personal Software Process (PSP) framework of the Software Engineering Institute (SEI). The proposal describes a specification of a software process for those developers who will begin their work on a telecommuting approach and doesn’t have this process defined so they can improve the development of their projects. Traditionally, a software professional is absent of a usual work ambiance and is subjected to his ways of going through development, it is possible that he or she doesn’t have a specific process for software developing or that he or she doesn’t know of one in particular. This article suggestion is focused on giving an improvement based on software processes that allows the developer the engagement of the particular challenges of telecommuting.